Cobb's Boston Tea Company at 71 and 73 Court Street, ca. 1890 - Unknown (Tufts Archival Research Center, 2005)
Street-level view north-northeast of (right to left) 71 and 73 Court Street, located at the northwest corner of Court Street and Cornhill. Commercial products are displayed in the storefront windows. Signage adorns both the facade and the southeast elevation of the buildings, which face southwest towards Court Street and southeast towards Cornhill respectively. A street sign is visible in the foreground of the photograph and pedestrians are included as well. 6 3/8 x 9 overall 6 15/16 x 9 15/16 Photographs